Asas Konsensualisme dalam Perjanjian Jual Beli Elektronik Perspektif Hukum Positif Indonesia - M. Jihan Febriza (RETORIKA: Journal of Law, Social, and Humanities, 2024)
This study aims to (1) analyze the construction of the principle of consensualism in electronic sales and purchase agreements based on Indonesian positive law; and (2) examine the implications of the application of the principle of consensualism on the legal certainty and binding force of electronic contracts. The study uses a normative legal method with statutory and conceptual approaches. he legal materials for this study were obtained from primary, secondary, and tertiary legal materials. All legal materials were analyzed through logical, systematic, and deductive legal reasoning, applying grammatical, systematic, teleological, and historical interpretations, which were constructed using legal theory and legal principles. The results of the study indicate that,  the first, the principle of consensualism remains the basis for the validity of electronic agreements, where agreements expressed through digital systems meet the requirements for a valid agreement, and electronic documents and signatures are legally recognized. Second, electronic contracts bind the parties, and their implementation must comply with the principles of legal certainty, good faith, justice, and consumer protection, thereby reinforcing the legitimacy, enforceability, and legal certainty of electronic transactions in Indonesia.